Pengembangan Sistem Informasi Pengelolaan Arsip Program Pembangunan Desa Kalembu Kanaika Kecamatan Wewewa Barat - Nimrod Renda Dadi; Stefanus D.I. Mau; Alexander Adis (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
The management of village development program archives plays a vital role in supporting effective, transparent, and accountable village governance. However, in many villages, including Kalembu KanaiKa Village in Wewewa Barat District, archive management is still conducted conventionally without the support of a structured information system. This condition creates several challenges, such as difficulties in accessing data, low administrative efficiency, and weak documentation and accountability of village development activities. Therefore, this study aims to examine the development of an information system for managing village development program archives based on local conditions and needs. The research seeks to identify the actual condition of archive management, analyze constraints faced by village officials, and formulate directions for developing an appropriate archive management information system in Kalembu KanaiKa Village. This study employed a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and document analysis involving village officials responsible for archive management and development program implementation. The results reveal that archive management has not been optimal due to limited human resources, inadequate facilities, and minimal use of information technology. Despite these limitations, village officials show readiness and willingness to adopt a simple and user-friendly archive management information system tailored to the village’s social and institutional capacity. These findings indicate that the development of archive information systems requires not only technical solutions but also attention to social, institutional, and capacity-building aspects.